FAKTOR RISIKO KEJADIAN MALARIA DI KAMPUNG ASEI BESAR DISTRIK SENTANI TIMUR KABUPATEN JAYAPURA TAHUN 2021 - Natalia Purba, Lilys Irianty; Jarona, Marlin Mayling; Purba, Ellen Rosawita Veronica (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Malaria cases in Asei Besar Village in the last 1 year there were 198 cases in 2020 and this is the third highest case in the Working Area of ​​the Kampung Harapan Community Health Center. This type of research is analytic observational, with a cross-sectional approach. This research was conducted in Asei Besar Village, East Sentani District. The sample technique used is purposive sampling. The number of samples is 50. The results of this research are the presence of stagnant water associated with the incidence of malaria with a p value of 0.021 (<0.05) The presence of bushes is associated with the incidence of malaria with a p value of 0.031 (<0.05) and the presence of cattle pens is associated with the incidence of malaria with a p-value of 0.034(<0.05). Suggestions for reducing the risk of malaria incidence are reducing bushes around the house, reducing standing water around the house, reducing cattle pens around the house